Scaling Rhizomatic Pedagogy: Strategies for Sustainable Implementation in Diverse Educational Contexts - Ismail Ismail (Universitas Muhammadiyah Enrekang, 2024)
Education in underserved settings often faces challenges due to rigid pedagogical approaches that limit student engagement and creativity. This study explores the impact of rhizomatic pedagogy on student engagement in a rural Indonesian elementary school, focusing on its ability to foster inclusive and interactive learning environments. The intervention involved 30 fifth-grade students over eight weeks, incorporating culturally relevant content, collaborative projects, and learner-directed activities. A mixed-methods approach combined pre- and post-intervention surveys with classroom observations and teacher interviews to assess engagement levels across cognitive, emotional, and behavioral dimensions. Results showed statistically significant improvements in engagement, with mean scores increasing for cognitive (3.45 to 4.12), emotional (3.22 to 3.98), and behavioral (3.18 to 4.05) dimensions. Qualitative findings highlighted enhanced participation, collaboration, and sustained focus, driven by activities that connected academic content to students’ lived experiences. The teacher emphasized the transformative role of student autonomy and cultural relevance in fostering deeper learning connections. The study’s findings have implications for curriculum design, teacher training, and educational policy, particularly in resource-constrained settings. Rhizomatic pedagogy demonstrates the potential to address key limitations of traditional teaching methods by promoting agency, inclusivity, and contextual learning. Future research should investigate its long-term impact and explore strategies for scaling its implementation in diverse educational environments. This study contributes to the discourse on innovative pedagogies, offering actionable insights for reimagining education in underserved contexts.